Strategies for Building Reputation of Tourism Destinations in Semarang Regency on Social Media - Rizki Halim; Mohammed Aden Suryana; Rachela Belinda Fatharani; Yofiendi Indah Indainanto (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyse the tourism promotion strategy implemented by the Semarang Regency Government through Instagram social media, specifically the @pesona_kabSemarang account. The promotion of attractions through social media is one aspect to support sustainable tourism and increase the number of visitors to the destination. The research method used a qualitative approach by selecting posts based on special features, natural and cultural tourism. The results showed that although there were several promoted events and activities, promotional strategies, there was still a lack of user interaction, such as the number of